Peningkatan Karakter Peduli Lingkungan Melalui Gerakan Literasi Lingkungan: Peran Guru Pendidikan Biologi - Jannah, Raudhatul; Manalu, Kartika; Jayanti, Ummi Nur Afinni Dwi (Medan Resource Center, 2024)
Environmental literacy refers to the process of educating and instilling a sense of environmental awareness and responsibility within a community. An effective environmental literacy program should be introduced at an early stage in an educational setting, especially in schools. Harapan Payabakung Private Senior High School has successfully implemented an environmental literacy curriculum within the school environment for two years. The school's environmental literacy program is a collaborative initiative between the Deli Serdang Education Office and Payabakung Village, aiming to address emerging environmental issues in 2021. This research used qualitative methodology, specifically using the analytic description method. Data for the field research was collected through interviews and documentation. The research findings on the environmental literacy movement at Harapan Payabakung Private Senior High School show that the movement has successfully fostered students' environmental awareness. However, there are still some challenges in the implementation of the program, particularly the lack of participation from all teachers in the school. Therefore, improvements need to be made to the environmental literacy program at Harapan Payabakung Senior High School to increase its effectiveness in the future.